A Clinical Audit of Fresh Frozen Plasma Usage - Hamid Iqbal, Farhat Abbass Bhatti, Nuzhat Salamat, Fahim Akhtar, Kashif Hafeez, (Journal of Rawalpindi Medical College, 2013)
Background: To assess the appropriateness of transfusions of fresh frozen plasma (FFP). Methods: In this cross sectional study use of FFP , by different departments, was analyzed. Management details and appropriateness, for the use of FFP, was recorded. British Committee for Standards in Haematology (BCSH) guidelines were used as standards. Results: Four hundred and ninety eight units of FFP were used during the study period for 118 transfusion episodes. Only 44% episodes of FFP transfusions were deemed appropriate. The most common inappropriate uses included bleeding with no coagulation test abnormality following cardiopulmonary bypass, hypovolaemia and hypoproteinaemia. The proportion of inappropriate request was similar between surgical and non surgical units. Conclusion: FFP is frequently used inappropriately